ELECTROPNEUMATIC DRIVE FOR INDUSTRIAL ROBOTS - Tadjiyev Xabibullo Xikmatovich, (Research Focus International Scientific Journal, 2026)
This scientific article presents the design of a newly developed electropneumatic drive for robots and robotic systems, the diagram of its operating principle, and the graphs of output shafts moving at different speeds and directions that are independent of each other. The proposed drive provides an opportunity to create intelligent modules for robots. The drive consists of electromagnets and pneumatic cylinders and, through the control system, ensures the movement of the output shafts at various speeds and steps. The proposed scientific article can be used by researchers and doctoral students conducting studies in the field of robotics.